Cloud point extraction for the determination of trace copper(II) in environmental samples using a new synthesized reagent and flame atomic absorption spectrometry - (:unkn) unknown (My University, 2013)
Cloud point extraction for the determination of copper(II) is proposed after the formation of a complex with sulfapyridylazo resorcinol (SPAR) and later measurement by flame atomic absorption spectrometry (FAAS) using Triton X-100 as a surfactant. The surfactant-rich phase was diluted with nitric acid in methanol, prior to FAAS measurement. Analytical parameters including pH, concentration of the chelating agent and surfactant, equilibration temperature and time were optimized.  The effects of matrix ions on the recovery of copper ions were also studied.  A detection limit of 1.64 μg L−1 along with an enrichment factor of 31 for Cu were achieved. The method was successfully applied to the determination of copper in tap water, stream water, rain water and a standard reference material.